Emergency thoracotomy. Issue 2 (June 1986) - Champion, H R; Danne, P D; Finelli, F
Abstract : Eighty-nine consecutive trauma patients, who were treated at one institution and received emergency thoracotomy, were studied. Although 76 (85%) of the patients had no vital signs at hospital arrival, 15 (17%) patients survived the emergency thoracotomy to progress to other hospital treatments. Ten patients were ultimately discharged, nine of whom have normal functions. Maintaining a broad set of indications for emergency thoracotomy may increase survival amongst trauma patients for whom the procedure is indicated.